Qualifications Frameworks Between Global and European Pressures and Local Responses - Borut Mikulec; Klara Skubic Ermenc (SAGE Open, 2016)
The article considers the Europeanization of education, a process that is taking place in the European Union (EU) as a result of the establishment of a common education policy and that is playing a part in determining the development of education policies in EU member states and candidate countries. The concept of Europeanization serves as a methodological tool with which to analyze one of the fundamental political instruments of European education policy, namely, the European Qualifications Framework (EQF), and also the national qualifications frameworks (NQFs) that are emerging under its influence. In the case of our analysis of the NQF that has been prepared by Slovenia, we demonstrate that the formulation of the EQF and NQFs in the EU is influenced by two factors: by the Anglo-Saxon countries, which were the first to establish a qualifications framework of the modern type, and by global neoliberal policy, with its tendency toward the deregulation, marketization, and commodification of education. At the same time, we tried to show that NQFs in continental Europe have resulted, by virtue of their local specificities, in frameworks that differ considerably from qualifications in the Anglo-Saxon countries. It appears that the effects of globalization and Europeanization on education are unpredictable, because policies are never simply copied into national systems.